1980
DOI: 10.1677/joe.0.0850105
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin Release in Hypogonadal and Normal Mice After Electrical Stimulation of the Median Eminence or Injection of Luteinizing Hormone Releasing Hormone

Abstract: Electrical stimulation of the median eminence, using parameters known to cause the release of LH in normal male mice, failed to elicit any gonadotrophin response in nypogonadal (hpg) male mice. Administration of 40 ng synthetic LH releasing hormone (LH-RH) resulted in release of LH from the pituitary gland of hpg mice, although the response was significantly lower than that of normal mice. These results were consistent with the hypothesis that the hypogonadal state of the hpg mouse results from a functional ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Implantation of an oestradiol-containing capsule had no significant effect on pituitary LH content or concentration in either hpg or normal mice. In order to economize on animals, control groups in which animals were injected with LH-RH followed by saline and vice versa were not included because previous studies in mice showed that sequential blood sampling either in untreated or saline-injected animals did not significantly alter plasma LH concentrations (Iddon, Charlton & Fink, 1980) and in rats the priming effect of LH-RH could not be elicited by injecting LH-RH followed by saline or vice versa (Aiyer et al 1974;Fink & Pickering, 1980). The reason for the difference in dosage of LH-RH required to produce a clear-cut and reproducible LH release in the present study compared with that used by Iddon et al (1980) is not readily apparent, although Iddon et al (1980) used male mice.…”
Section: Resultsmentioning
confidence: 99%
“…Implantation of an oestradiol-containing capsule had no significant effect on pituitary LH content or concentration in either hpg or normal mice. In order to economize on animals, control groups in which animals were injected with LH-RH followed by saline and vice versa were not included because previous studies in mice showed that sequential blood sampling either in untreated or saline-injected animals did not significantly alter plasma LH concentrations (Iddon, Charlton & Fink, 1980) and in rats the priming effect of LH-RH could not be elicited by injecting LH-RH followed by saline or vice versa (Aiyer et al 1974;Fink & Pickering, 1980). The reason for the difference in dosage of LH-RH required to produce a clear-cut and reproducible LH release in the present study compared with that used by Iddon et al (1980) is not readily apparent, although Iddon et al (1980) used male mice.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the hypogonadal (hpg) mouse it was observed that administration of 40 ng of a GnRH analog could immediately trigger LH secretion from the pituitary, albeit significantly lower than that in normal mice [62]. In the rhesus monkey (Macaca mulatta), the responsiveness of pituitary gonadotropes to GnRH stimulation is clearly enhanced by a preceding chronic pulsatile infusion of GnRH [63].…”
Section: Kiss1r Displays Basal Constitutive Signaling and Kp-independmentioning
confidence: 99%
“…That the mutation results in an absence of endogenous GnRH secretion has been demonstrated by experiments in which injection of synthetic GnRH increases pituitary content and circulating levels of gonadotropin, as well as gonadal weight (Fink et al, 1982;Young et al, 1983), while electrical stimulation of the hypothalamus has no effect (Iddon et al, 1980). This mutant has been used by several investigators as a model to study the anatomy and physiology of the hypothalamic GnRH system.…”
Section: The Hypogonadal Mousementioning
confidence: 99%